The gap gene Krüppel of Rhodnius prolixus is required for segmentation and for repression of the homeotic gene sex comb-reduced - Lavore, Andres Esteban (2014)
The establishment of the anterior–posterior segmentation in insects requires the concerted action of a hierarchical gene network. Here, we study the orthologue of Krüppel gap gene in the hemipteran Rhodnius prolixus (Rp-Kr). We characterized its structure, expression pattern and function. The genomic sequence upstream of the Rp-Kr transcriptional unit shows a putative regulatory region conserved in the orthologue genes from Drosophila melanogaster and Tribolium castaneum. Rp-Kr expression is zygotic and it is expressed in the anterior half of the embryo (the posterior half of the egg) during the blastoderm stage and germ band formation; later, during germ band extension, it is expressed in a central domain, from T2 to A3. The Rp-Kr loss of function phenotypes shows disrupted thoracic and abdominal segmentation. Embryos with weak segmentation phenotypes show homeotic transformations, in which an ectopic tibial comb, typical of T1 leg, appears in T2, which correlates with the ectopic expression of Rp-sex-comb reduced in this leg.